2021
DOI: 10.1016/j.scs.2020.102688
|View full text |Cite
|
Sign up to set email alerts
|

Surface and satellite observations of air pollution in India during COVID-19 lockdown: Implication to air quality

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 46 publications
6
61
0
2
Order By: Relevance
“…Several choices have been carried out for comparing the 2020 dataset with baseline conditions based on multi-year averaged data. Dantas et al (2020), Tobías et al (2020), and Navinya et al (2020) suggested the comparison with the same values obtained in 2019; Li et al (2020) , and Sathe et al (2021) with averaged values over the 3 previous years 2017-2019; and Kanniah et al (2020) with 5-years period 2015-2019. Ambient pollutants concentrations are strongly influenced by meteorological conditions and emission sources, exhibiting thus pronounced seasonal patterns.…”
Section: Methodssupporting
confidence: 57%
See 1 more Smart Citation
“…Several choices have been carried out for comparing the 2020 dataset with baseline conditions based on multi-year averaged data. Dantas et al (2020), Tobías et al (2020), and Navinya et al (2020) suggested the comparison with the same values obtained in 2019; Li et al (2020) , and Sathe et al (2021) with averaged values over the 3 previous years 2017-2019; and Kanniah et al (2020) with 5-years period 2015-2019. Ambient pollutants concentrations are strongly influenced by meteorological conditions and emission sources, exhibiting thus pronounced seasonal patterns.…”
Section: Methodssupporting
confidence: 57%
“…They noted that the reduction of anthropogenic activities (namely tanneries, chemical, and cast-iron industries), of traffic, as one of the biggest concerns in Kolkata, and a complete ban on construction activities have accelerated the reduction of air pollution. Recent studies also reported that NO2 ( Sathe et al, 2021 ) and PM2.5 ( Kumar et al,2020 ) reductions in Indian cities are comparable to the reductions observed in Asian and European cities. Paradoxically, while Biswal et al (2020) and Vadrevu et al (2020) argued that the highest reduction of tropospheric NO2 in New Delhi may be due to a reduction in vehicular emissions, which is the major pollutant source in the region, they estimated that in some Indian regions, there was an increase in NO2 concentrations observed during the lockdown.…”
Section: Discussionmentioning
confidence: 80%
“…Most of the region comes near to the satisfactory level of AQI as per the Government norms during the lockdown. Improvement in AQI and ER% was observed in all the districts due to reduced industrial operations, agriculture practices like residue burning, and transport activities as a result of COVID-19 driven lockdown enforcement [1,5,6,9,10,14,17]. This analysis showed the industrial pollution was prevailing during the lockdown and highlighted the places of industrial operations even in lockdown enforcement conditions.…”
Section: Impact Of Covid-19 On Aqi and Er%mentioning
confidence: 72%
“…Satellite-based air quality assessments in terms of pollutant concentrations, AQI, and ER%, were done using satellite measurements in COVID-19 (April 2020) and NON-COVID (April 2019) scenarios over Haryana, situated in the Northern part of India. The selection of period was done, with the assumption, that the COVID-19 driven lockdown would have resulted in the reduction of pollutant level in the study area as reported for other parts of the world [9,14,15,18,19,25,26]. Validation showed a high correlation between satellites measured concentration of air pollutants with that of ground-based pollutants (r 2 = [ 0.5, p = 0.00).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation